2012
DOI: 10.3109/1354750x.2012.709882
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 concentrations in patients with advanced gastric cancer and its relation with treatment

Abstract: Our results indicated that netrin-1 concentrations elevated in advanced gastric cancer compared to a healthy control group and netrin-1 concentrations decreased with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
13
0
4
Order By: Relevance
“…As a result, aspirin preserved the synthesis of secreted netrin-1 under pro-inflammatory conditions, thus counteracting monocyte/macrophage plaque accumulation. Future clinical investigations are needed to verify the applicability of these findings to human atherosclerosis, as well as to non-cardiovascular diseases including neurological disorders (Rajasekharan and Kennedy, 2009 ; Izzi and Charron, 2011 ) and cancer (Delloye-Bourgeois et al ., 2012 ; Kefeli et al ., 2012 ; Ko et al ., 2012 ) where aspirin has also been reported to exert protective actions (Algra and Rothwell, 2012 ; Rothwell et al ., 2014 ,b 2012a ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, aspirin preserved the synthesis of secreted netrin-1 under pro-inflammatory conditions, thus counteracting monocyte/macrophage plaque accumulation. Future clinical investigations are needed to verify the applicability of these findings to human atherosclerosis, as well as to non-cardiovascular diseases including neurological disorders (Rajasekharan and Kennedy, 2009 ; Izzi and Charron, 2011 ) and cancer (Delloye-Bourgeois et al ., 2012 ; Kefeli et al ., 2012 ; Ko et al ., 2012 ) where aspirin has also been reported to exert protective actions (Algra and Rothwell, 2012 ; Rothwell et al ., 2014 ,b 2012a ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of netrin-1 in the spread of cancer cells was corroborated by the finding that especially metastatic breast carcinomas show netrin-1 overexpression compared to their non-metastatic counterparts [9]. However, since netrin-1 is strongly overexpressed in various cancer entities, it has been presented as a pluripotent tumor biomarker independent of the grade of malignancy or tumor subtype [10][12]. For some cancer subtypes such as adenocarcinomas of the pancreas, it was demonstrated that netrin-1 is either associated with significantly earlier relapse or worse patient overall survival [13].…”
Section: Introductionmentioning
confidence: 92%
“…[14][15][16] There is also evidence showing that netrin-1 acts as a proangiogenic factor through Unc-5 Netrin Receptor B (UNC5B) and extracellular-signal-regulated kinase (ERK)-1/2-endothelial nitric oxide synthase (eNOS) mechanism to enhance tumor angiogenesis, thereby driving tumorigenesis. [14][15][16][17][18][19] Papanastasiou et al 20 have demonstrated that netrin-1 is strongly expressed in ovarian malignant tumors but not in nontumor tissues, suggesting that netrin-1 may represent a new biomarker for ovarian cancer, whereas how netrin-1 regulates the growth of ovarian cancer remains uncertain. In this study, we sought to investigate the role of SOX6 and netrin-1 in regulating the biological properties of ovarian cancer cells and the relationship between SOX6 and netrin-1 expression in the cells.…”
Section: Introductionmentioning
confidence: 99%